The genus Scirtothrips (Thysanoptera: Thripidae) in Malaysia, with four new species and comments on Biltothrips, a related genus - Ng, Y.f.; Mound, L.a.; Azidah, A.a. (Zootaxa, 2014)
Species of the genus Scirtothrips are studied from Malaysia for the first time. Six species of this genus are here recorded from Malaysia: S. dobroskyi is newly recorded, and four new species: S. lantanae sp.n., S. lixinae sp.n., S. hitam sp.n. and S. malayensis sp.n. are described together with an illustrated identification key. Relationships were examined between S. dorsalis and the closely related S. hitam sp.n., based on the mitochondrial gene COI, and a redescription of the widespread pest species, dorsalis, is provided. Biltothrips minutus (Bhatti) is reported from Malaysia for the first time, and illustrations provided to distinguish this genus from Scirtothrips.